The Fragility Index in peri‐operative randomised trials that reported significant mortality effects in adults. (26th April 2019) - Bertaggia, L.; Baiardo Redaelli, M.; Lembo, R.; Sartini, C.; Cuffaro, R.; Corrao, F.; Zangrillo, A.; Landoni, G.; Bellomo, R.
Summary: More than one million peri‐operative patients die each year. Thus, small improvements in peri‐operative care may save thousands of lives. However, clinicians need confidence in the robustness of trial findings. The Fragility Index may complement frequentist analysis and provide quantitative assessment of robustness. We searched MEDLINE for peri‐operative critical care randomised controlled trials that reported a statistically significant difference in mortality. We identified 46 trials with 37, 347 participants. The median (IQR [range]) Fragility Index was 2 (1–3 [0–49]). Eleven trials had a Fragility Index of zero (changing from the Chi‐square test to Fisher's exact test removed significance) and seven trials had a Fragility Index of 1. Only 23/46 trials had a Fragility Index greater than the number of patients lost to follow‐up. There was a strong positive correlation between the Fragility Index and: the number of participants, R 2  = 0.97, p < 0.0001; the number of centres that recruited participants, R 2  = 0.96, p < 0.0001; the number of nations that recruited participants, R 2  = 0.93, p < 0.0001; and the number of deaths, R 2  = 0.97, p < 0.0001. As measured by the Fragility Index, the effect of peri‐operative interventions on mortality in individual randomised controlled trials are not robust.